Professionalisierung von Grundschullehrkräften Kontext, Bedingungen und Herausforderungen - Mammes, Ingelore; Rotter, Carolin (Verlag Julius Klinkhardt, 2022)
On the one hand, expectations of primary school teachers are high. On the other hand, a specific pedagogical professionalism of primary school teachers is doubted again and again. In fact, a compilation of requirements and competences that apply specifically to primary school teachers does not yet exist. While in the discourse on professional theory, challenges for and demands on the professionalism of secondary school teachers seem to be discussed and empirically developed, in the discourse on primary school pedagogy, methodological-didactic questions as well as structural framework conditions come into view, without grasping the consequences for the actions of primary school teachers and framing them in terms of professional theory. The aim of this volume is therefore to link the two discourses more closely and to look at the professionalisation of primary school teachers from different perspectives.